Towards holistic inclusion in Malaysia: knowledge of special education needs among in-service distant - Saad, Supiah; Ibrahim, Haniz; Nayan, Nordina (2013)
The findings of previous researches showed that mainstream teachers' have a negative attitude towards students with special educational needs (SEN) in Malaysia due to the lack of information and awareness. The purpose of this study was to determine the knowledge level of SEN among experienced mainstream teachers in Malaysia. A survey was distributed among 147 teachers undergoing distance learning Bachelor of Education (BEd) degree in a public university. Teaching experience and familiarity with SEN persons did not affect the knowledge level of the three groups of participants. The results of the study revealed that teachers had a moderate level of knowledge on SEN. The implication of these findings for inclusion and for future research in Malaysia is also provided. This study also made recommendations on how to improve the knowledge level of SEN inservice teachers in Malaysia, and the need to assess the knowledge on SEN among parents, paraprofessionals, educational administrators and other stake holders in order to achieve holistic inclusion for pupils with SEN.